Focus on curriculum - McInerney, Dennis M.; Van Etten, Shawn (Research on sociocultural influences on motivation and learning ;, 2005)
There are many teaching and curriculum programs that attempt to make education relevant to the wider sociocultural environment of learners. Volume 5 focuses on research on curriculum and teaching from a sociocultural perspective. Authors will discuss exemplary examples of research on curriculum initiatives, teaching resources, and teaching approaches that reflect a concern for sociocultural issues broadly defined, while also mapping out implications, future issues, and future research agendas. There will be chapters on reading mathematics, science, language, social science, history, music, health education, religious and moral education, information technology, vocational education, and multicultural studies. The text will be relevant to educators across all levels of education.